Landasan Teoritis Pengembangan Kurikulum Pendidikan Agama Islam - Hudiyanto, Amin; Tasman Hamami; Syakur Wildan (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
The Islamic religious education curriculum needs to balance this by developing the existing curriculum by utilizing technology and science to be used as more efficient methods and media. In discussing the development of Islamic education curriculum and also the decision of the Minister of Religion regarding the curriculum in madrasas. This is related to several aspects such as the nature of the Islamic religious education curriculum, the development of the Islamic religious education curriculum according to the figures, and the theoretical basis for the development of the Islamic religious education curriculum. The development of the Islamic religious education curriculum is an important component in the world of education which refers to the preparation and planning of learning, the learning process or implementation, and also the evaluation of learning to assess whether or not a lesson has been achieved in an institution in particular or in general. By studying the development of Islamic religious education curriculum according to experts and leaders and used properly to develop an Islamic religious education curriculum that is appropriate and effective in achieving the goals of Islamic religious education.